New species, new records, and new synonymy in Hemilophini (Coleoptera, Cerambycidae, Lamiinae) - Heffern, Daniel; Botero, Juan Pablo; Santos-Silva, Antonio (Zootaxa, 2019)
A new species, Hemierana rileyi sp. nov., is described from the USA (Texas). Tyrinthia lycinella Bates, 1881 is synonymized with T. xanthe Bates, 1881. A new country record (Panama), and a new province record in Costa Rica (Limón) is given for Eranina cretaria (Galileo & Martins, 2005), and a new country record (Panama) is given for Eranina costaricensis (Galileo & Martins, 2005).